2015
DOI: 10.1007/s40674-014-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Management of Gastrointestinal Involvement in Scleroderma

Abstract: Gastrointestinal tract (GIT) commonly affects patients with systemic sclerosis (SSc). The GI involvement is quite heterogeneous varying from asymptomatic disease to significant dysmotility causing complications like malabsorption, weight loss and severe malnutrition. This review focuses on the management of GI involvement in SSc and has been categorized based on the segment of GIT involved. A brief discussion on the role of patient reported outcome measures in SSc-GI involvement has also been incorporated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(121 citation statements)
references
References 130 publications
0
104
0
Order By: Relevance
“…Although this study looked only at symptomatic endpoints rather than pH‐impedance testing, the findings suggest that there may be a role for these additional therapies in SSc patients. Promotility agents may improve LES tone and gastric emptying, thus improving reflux control, although the effects on esophageal contractility may wane with progressive smooth muscle atrophy and fibrosis …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this study looked only at symptomatic endpoints rather than pH‐impedance testing, the findings suggest that there may be a role for these additional therapies in SSc patients. Promotility agents may improve LES tone and gastric emptying, thus improving reflux control, although the effects on esophageal contractility may wane with progressive smooth muscle atrophy and fibrosis …”
Section: Discussionmentioning
confidence: 99%
“…Up to 80% of patients with SSc have esophageal involvement . The most common esophageal disorder in SSc patients is gastro‐esophageal reflux disease (GERD) . Complications from esophageal reflux can be serious and include bleeding, stricture formation, Barrett's esophagus, and adenocarcinoma .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic regimens often include (a) anti‐emetics for nausea and vomiting, (b) proton pump inhibitors and histamine‐2 receptor blockers for reflux symptoms, (c) antibiotics for small intestinal bacterial overgrowth (SIBO), (d) antidiarrheal agents or laxatives for bowel dysmotility and (e) prokinetics for dysmotility. Despite the wide array of medications listed above, their effect is very limited, especially when significant smooth muscle fibrosis has occurred …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Gastrointestinal tract (GIT) involvement commonly affects patients with SSc, causing complications like malabsorption, weight loss and severe malnutrition [20]. In a recent study, it was reported that the Total GIT Score provides greater discrimination between mild, moderate, and severe self-rated GIT involvement than individual scales [21].…”
Section: Survival In Sscmentioning
confidence: 99%